2021
DOI: 10.3390/su13169162
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Tourism Recovery in the Post-COVID-19 Period: An Evolutionary Game Theory Approach

Abstract: This study aims to explore the process of tourism recovery in the post-COVID-19 period and the role of stakeholders in promoting such a process. Using evolutionary game theory, this study analyzes the behavior interactions and game equilibrium of stakeholders in the development of tourism by constructing an evolutionary game model amongst governments, tourists and tourism enterprises. Then, the influences of different evolution paths and major parameters affecting stakeholders’ strategy selection are discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…ESS is used to describe a strategy, that is, when the majority of individuals in the population choose a strategy, the group that chooses the mutation strategy cannot invade the group containing the majority of individuals, because it contains fewer individuals, so ESS has good stability in the process of the evolutionary game [ 45 ]. RD was proposed by Taylor and Jahnke [ 46 ], it refers to the ability of individuals to frequently adjust themselves through imitation, learning, and selection of the current situation [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…ESS is used to describe a strategy, that is, when the majority of individuals in the population choose a strategy, the group that chooses the mutation strategy cannot invade the group containing the majority of individuals, because it contains fewer individuals, so ESS has good stability in the process of the evolutionary game [ 45 ]. RD was proposed by Taylor and Jahnke [ 46 ], it refers to the ability of individuals to frequently adjust themselves through imitation, learning, and selection of the current situation [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…As the behaviors of tourism stakeholders affected by the pandemic are complex and change over time, the future growth of tourism cannot be judged based on how the pandemic is affecting it now or by comparing it to other public crises. Implementing the evolutionary game method to the evolution interpretation of tourism recovering under the impact of the pandemic can help explain how the behaviors of tourism stakeholders are affected by the pandemic, make policy suggestions for tourism recovery, and reduce the effects of the global epidemic on the tourism sector [54] .…”
Section: Sars-cov-2 Variantsmentioning
confidence: 99%
“…Yan et al [17] aimed to explore the process of tourism recovery in the post-COVID-19 era. By constructing an evolutionary game model between the government, tourists, and tourism enterprises, he found that the development and change of public health emergencies affect the behavioral strategies of tourism stakeholders.…”
Section: Literature Reviewmentioning
confidence: 99%